INOVASI PRODUK DAN EKSPEKTASIINOVASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Jony Oktavian Haryanto; Jeane Polluan (Journal of Management and Business, 2009)
Product innovation is an important element in consumer buying decision for high technology product including mobile phone. Therefore, it is quite important to know the role of product innovation in consumer buying decision. The purpose of this research is to identify the effect of product innovation, forthcoming innovation, and preference to delay present purchase on consumer buying decision. This research found that preference to delay purchase influence consumer buying decision positively. However, product innovation does not influence consumer buying decision significantly. Moreover, product innovation influences the forthcoming innovation positively as well as affects consumer preference to delay purchase. On the other hand, the forthcoming innovation influences consumer buying decision negatively.